PERANCANGAN SISTEM INFORMASI PENGELOLAAN TABUNGAN KOPERASI WIN SYARIAH SMK WIDYA NUSANTARA SUMEDANG - Andriansah, Deby; Budiman (Universitas Majalengka, 2025)
Koperasi WIN Syariah, a cooperative for the employees of SMK Widya Nusantara Sumedang established in 2007, plays a vital role in improving the welfare of its members through its mini bank and school supply business units, operating on Wadi'ah and Mudharabah principles. However, its operational processes, including the management of member data, savings, and loans, are still conducted manually. This traditional approach leads to significant challenges, such as time-consuming data management, a high potential for human error in transaction recording, and inefficiencies in financial reporting. In response to the rapid advancement of technology, the integration of an information system has become essential to address these issues. This paper details the development of a web-based Savings Management Information System for Koperasi WIN Syari’ah. The system is designed to automate and streamline core cooperative functions, from member data administration and transaction processing to the automatic generation of financial statements. The objective of this system is to provide a comprehensive solution that mitigates the problems associated with manual record-keeping. It is expected that the implementation of this information system will significantly enhance operational efficiency, improve data accuracy, and provide more transparent and timely financial reporting, thereby supporting the cooperative's mission to advance the prosperity of its members.